(3efgGL GdHjGf ajeG jSJYedg GdEfSGfs - (3jMji Hf YjSi Hf LRdI GdHZOGOj, CHh Ydj,J (B493 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi XgQJ eUfhYGJg cd eG JHdZg Gdgee, hjJbQH Hg Cgd GdYde ef GdNOe , eSJbUQ Pdc s
(3BNQgG (B:s
(3hgh MGQ jGHS , jSgd GdHdZe , hbO ESJhai PcQg ai TQMI ai HGH GdKfGA , hddg GdMeO s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B161 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B218s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B187 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1870s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdWHs